Integrated health interventions for improved livelihoods: a case study in Ethiopia - Kassie, M.; Abro, Z.; Wossen, T.; Ledermann, S.; Diiro, G.; Ballo, S.; Belayhun, L. (MDPI, 2020)
Smallholder farmers in sub-Saharan Africa (SSA) face multifaceted and co-existing risks, such as human and animal diseases and pests. Even though smallholder farmers often experience these challenges simultaneously, interventions to address these challenges are often implemented in a piecemeal fashion. However, managing agricultural production constraints without alleviating human and livestock health burdens might not generate significant and sustained benefits to achieve the desired development outcome (e.g., reducing hunger, malnutrition, and poverty). As such, building farmers’ resilience and adaptive capacity to co-existing production constraints and health burdens may require an integrated and holistic approach. Understanding the potential benefits of an integrated approach would provide critical information, for example, for revisiting the extension systems and for designing pro-poor holistically integrated interventions to tackle interrelated challenges facing smallholder farmers. In this paper, we examined the economic benefits of integrated human–plant–animal health interventions aimed at controlling malaria, stemborer infestations of crops, and trypanosomiasis, along with beekeeping as a livelihood diversification option in rural Ethiopia. We developed a whole-farm multiperiod mathematical linear programming model to examine the economic consequences of the interventions. Our results suggest that relaxing livelihoods and the human–plant–animal health constraints that farmers face has the potential to at least double income. The results further show that exploiting the potential synergies among interventions can generate higher economic benefits. The annual income from the combined interventions is 35% higher than the sum of the income gains from each intervention alone. Our results support an integrated approach to achieve holistic outcomes in areas where these development constraints co-exist.